Intestinal permeability in the ileal pouch. Issue 2 (August 1996) - Merrett, M N; Soper, N; Mortensen, N; Jewell, D P
Abstract : BACKGROUND: Villous atrophy, mucin changes ('colonic metaplasia'), and chronic inflammation occur to varying degrees in all patients with ileal pouchanal anastomosis whereas acute inflammation (pouchitis) affects a subgroup of patients with prior ulcerative colitis. AIM: To measure epithelial barrier function looking for possible functional adaptation in ileal 'pouch' mucosa. PATIENTS: Patients with an ileal pouch prior to ileostomy closure (n = 12), functioning pouch (n = 14), pouchitis (n = 8), and ulcerative colitis (n = 12) were assessed. METHODS: 51Cr-EDTA was administered into the 'pouch' or rectum and urinary recovery over 24 hours was taken as an indication of permeability (barrier function). Histological analysis of 'pouch' biopsy specimens was undertaken. RESULTS: Mucosal permeability is decreased from median 9.4% (range 5.4% to 39.1%) to 1.4% (range 0.38% to 2.2%) after ileostomy closure (p < 0.002) with levels being negatively correlated with two histological parameters of colonic metaplasia-mucin changes (p = 0.03) and villous atrophy (p = 0.05). Pouchitis was associated with increased permeability 5.9% (1.9% to 19.5%) compared with healthy 'pouch' 1.4% (0.35 to 2.2%) (p < 0.006). CONCLUSION: Despite the presence of chronic inflammation in the mature 'pouch' functional adaptation with reduced permeability occurs in conjunction with colonic metaplasia.